“COVID-19 affected me greatly (sigh), imagine I'm being called a mother and yet I'm also a child”: the effect of COVID-19 on fertility management practices among women in Nairobi and Kisumu cities, Kenya - Kwena, Zachary Arochi; Wekesa, Pauline; Gitome, Serah; Okumu, Sarah; Ndunyu, Louisa; Bukusi, Elizabeth; Himes, Emily; Holt, Kelsey; Liu, Jenny; Vallin, Janelli; Suchman, Lauren (Frontiers in Global Women's Health, 2025)
BackgroundThe COVID-19 pandemic strained the provision of sexual and reproductive health services, including family planning, which were categorized as non-essential services at the peak of COVID-19 infection control in Kenya. We set out to assess the effect of COVID-19 on fertility management practices among Kenyan women in two cities to inform mitigation measures in future similar disruptions.MethodsThis was a qualitative study to describe the effect of the COVID-19 pandemic on women's fertility management practices from 61 in-depth interviews (IDIs) with women aged 15–45 years residing in Nairobi and Kisumu, Kenya, between February and May 2021. Identified participants were consented and interviewed at convenient locations. We used a constant comparative analysis that compared emergent themes across topics and transcripts to identify and group those that are similar or dissimilar to arrive at insights that informed our conclusions.ResultsOur findings show that COVID-19 affected women's fertility management practices at individual, interpersonal, and organizational levels. At the individual level, lack of money due to COVID-19-induced economic difficulties made family planning services unaffordable to women. Other women delayed their conception plans until their financial situation improved. At the interpersonal level, travel restrictions separated couples, making it challenging for those who had plans to conceive to actualize their fertility plans. Additionally, women who reported to be sexually inactive relaxed adherence to their contraceptive use schedule because of the reduced risk of unintended pregnancy. Finally, at the organizational level, provider shortages, long queues, and contraceptive stockouts during COVID-19 compromised women's access to family planning services. We also found that a minority of women who were either not using contraceptives or who were on long-acting methods perceived little or no effect of COVID-19 on their fertility management practices.ConclusionCOVID-19's effect on women's fertility management practices manifested at individual, interpersonal, and organizational levels. There is a need to devise strategies that empower women to deal with their family planning needs and those that make healthcare systems resilient enough to handle the effects of emergent crises without compromising the provision of existing services.